The Impact of The Independent Learning Curriculum's Development on Mathematics Education - Kusuma, Anggun Badu; Dewi, Resti Putri Rahma (Al-Khawarizmi, 2024)
The curriculum is a set of educational program plans used as guidelines for implementing learning activities to achieve national education goals. The independent curriculum is newly established in Indonesia and will undoubtedly influence learning, including mathematics. This research aims to analyse the impact of changes to the independent curriculum on mathematics learning. This research uses the Systematic Literature Review (SLR) method by reviewing articles and identifying, analysing, and concluding several studies that have been conducted previously. Article searches were done using the Google Scholar search engine and the publish or perish application. The research results found that the development of the independent curriculum had a significant influence on mathematics learning. The positive impact of implementing mathematics learning is that students' abilities in mathematics increase, and teachers can increase their ability to innovate and be creative. Meanwhile, the negative impact of implementing mathematics learning is that there are still insufficient teachers and difficulty creating learning tools.